(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study investigates 5 Star Virtual Assistants, a Philippine-based outsourcing company located in Iloilo City that delivers a range of virtual assistant services to support business operations. The research aims to propose a strategic retention plan to enhance employee engagement and reduce turnover in a remote work environment. By identifying key factors influencing employee satisfaction and commitment, the study seeks to provide actionable insights that will strengthen retention strategies, increase productivity, and improve overall organizational performance. This study adopts a descriptive-correlational research design to examine the connection between remote work and employee retention. A total of 206 virtual assistants from 5 Star Virtual Assistants in Iloilo City participated in the study, selected through purposive sampling. Data were collected between December 2024 and April 2025 through an online survey distributed via Google Forms. The study reveals that out of 206 respondents, the majority (64.5%) are female, and a significant portion (72.27%) are between 18 to 27 years old. In terms of tenure, 67.27% have been with the company for 0–2 years, 17.73% for 3–4 years, and 15% for 5 years or more, indicating a predominantly new workforce. The findings indicate that the company’s remote work setup significantly influences employee retention. Respondents expressed positive perceptions of the work culture, work-life balance, and communication, each with a composite mean of 3.35. Compensation and benefits were viewed as satisfactory (composite mean = 3.23), while the organizational culture—promoting collaboration and innovation—further contributed to retention (composite mean = 3.30). Additionally, employees strongly agreed that career development opportunities are available (composite mean = 3.34), reinforcing the company’s role in supporting employee growth and engagement. This study underscores the pivotal impact of remote work policies on employee retention in a business process outsourcing company based in Iloilo City. The proposed retention plan addresses critical areas including workplace culture, work-life balance, communication effectiveness, compensation and benefits, organizational values, and opportunities for career growth. Enhancing these dimensions is expected to promote sustained employee engagement, reduce turnover, and boost overall productivity and organizational success.